Single progesterone receptor-positive phenotype has the similar clinicopathological features and outcome as triple-negative subtype in metastatic breast cancer - Luo, Yunbo; Pu, Hongyu; Li, Fangwei; Qian, Shuangqiang; Chen, Jingtai; Zhao, Xiaobo; Hou, Lingmi (Frontiers in Oncology, 2023)
Objective: The same clinicopathological features and prognosis have been reported between single progesterone receptor-positive (sPR-positive) and triple-negative phenotype in early-stage breast cancer, but such similarity has not been studied in metastatic breast cancer (MBC). Therefore, the purpose of this study was to estimate the difference between sPR-positive phenotype and other phenotypes in MBC. Methods: Patients with HER-2-negative MBC were selected from the Surveillance, Epidemiology and End Results database. Pearson’s χ2 test was used to compare the difference of clinicopathologic factors between sPR-positive phenotype and other phenotypes. Univariate and multivariate analyses were performed to evaluate the effects of hormone receptor (HoR) phenotypes and other clinicopathologic factors on the cancer-special survival (CSS) and overall survival (OS). Results: Finally, 10877 patients including 7060 patients (64.9%) with double HoR-positive (dHoR-positive), 1533 patients (14.1%) with single estrogen receptor-positive (sER-positive), 126 patients (1.2%) with sPR-positive and 2158 patients (19.8%) with double HoR-negative (dHoR-negative) were analyzed. The patients with sPR-positive or dHoR-negative were more likely to be younger, higher grade and tumor stage, visceral and brain metastasis than ER-positive phenotypes (P<0.001). MBC with sPR-positive had the similar CSS (HR: 1.135, 95%CI: 0.909-1.417, P=2.623) and OS (HR: 1.141, 95%CI: 0.921-1.413, P=0.229) as dHoR-negative, but worse outcome than ER-positive phenotypes. Chemotherapy significantly improved the survival for MBC, especially for sPR-positive MBC (CSS, HR: 0.39, 95%CI: 0.213-0.714, P=0.002; OS, HR: 0.366, 95%CI: 0.203-0.662, P=0.001). Conclusions: Patients with sPR-positive and triple-negative have similar biological behavior and prognosis in MBC. Chemotherapy may be a preferred recommendation for MBC with sPR-positive.